A comparison of bryophyte diversity in the Macaronesian Islands: island versus habitat approach - González-Mancebo, Juana M. (2014)
In this paper, we present a comparison of richness patterns and floristic similarity for bryophytes in the five most important altitudinal habitat types in the Macaronesian islands. We evaluate the importance of different factors discussed in the literature in predicting species diversity applying the traditional island approach and within the framework of the new habitat approach, including area, isolation, climatic factors, geological age and human influence. From the analysis of patterns of bryophyte species distribution for selected habitats across islands and archipelagos, we specifically test the hypothesis that (i) floristic similarity is primarily determined by climatic factors, but not by geographical distance due to high dispersal ability in this species group and (ii) bryophyte richness is best predicted by area, but not by geological age of the habitat due to very low endemicity or speciation rate and high colonization rate.